2018
DOI: 10.1177/1849454418786159
|View full text |Cite
|
Sign up to set email alerts
|

Placental protein 13

Abstract: Placental protein 13 (PP13), a glycan binding protein predominantly expressed in syncytiotrophoblast, dimeric in nature, lacks N-terminal signal peptide, bypasses the endoplasmic reticulum, and secretes into maternal circulation as exosomes or microvesicles. PP13 has jelly roll fold conformation with conserved carbohydrate recognition domain which specifically binds to β-galactosides of the glycan receptors during placentation. PP13 binds to glycosylated receptors on human erythrocytes and brings about hemaggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 136 publications
0
19
0
Order By: Relevance
“…Recently, Martin et al 55 showed that the e Hsp‐27 concentration increases up to twofold in the first and second trimesters in patients with PE compared with healthy term patients. Also, this was associated with a decrease in placental protein‐13, which is involved in normal placentation 56,57 . Unfortunately, in this study, the functional role of e Hsp‐27 in the regulation of the inflammatory response was not addressed.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, Martin et al 55 showed that the e Hsp‐27 concentration increases up to twofold in the first and second trimesters in patients with PE compared with healthy term patients. Also, this was associated with a decrease in placental protein‐13, which is involved in normal placentation 56,57 . Unfortunately, in this study, the functional role of e Hsp‐27 in the regulation of the inflammatory response was not addressed.…”
Section: Discussionmentioning
confidence: 85%
“…Also, this was associated with a decrease in placental protein-13, which is involved in normal placentation. 56,57 Unfortunately, in this study, the functional role of eHsp-27 in the regulation of the inflammatory response was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…PP13 is a glycan-binding protein mainly expressed in syncytiotrophoblast and secreted into the maternal circulation via exosomes or microvesicles [ 38 ]. Although an earlier observational study showed an association between low first trimester PP13 concentrations in maternal serum and FGR [ 39 ], subsequent studies [ 33 , 40 ] found limited predictive utility with no significant differences in median PP13 MoM levels in FGR-affected pregnancies even when combined with other first trimester screening markers such as PAPP-A [ 33 ] and ADAM12 [ 40 ].…”
Section: Hormonal Factors Polypeptides and Glycoproteinsmentioning
confidence: 99%
“…It is decreased in the early stage of preeclampsia and increased in the later stage and through regulating the release of prostacycline to reshape the maternal spiral artery of the early placenta [35].…”
Section: Preeclampsiamentioning
confidence: 99%